Porous Co3V2O8Nanosheets with Ultrahigh Performance as Anode Materials for Lithium Ion Batteries - Zhang, Q.; Pei, J.; Chen, G.; Bie, C.; Sun, J.; Liu, Jian (Wiley-VCH Verlag, 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim In order to realize high performance electrode for long-lived lithium ion batteries (LIBs), engineering microstructures of electrode materials, especially porous, hollow, and hierarchical nanostructures, holds great promise in preventing the capacity fading stem from mechanical stress and volume change. Here, this paper reports a facile strategy to fabricate porous Co 3 V 2 O 8 nanosheets with large surface-to-volume ratio via a dehydration process using Co 2 V 2 O 7 ·3.3H 2 O as precursor. Benefiting from layer-to-layer nanosheets with mesoporous structure created form electrochemical reconstruction, the Co 3 V 2 O 8 electrode exhibits ever-increasing lithium storage capacity after a period of fading. When cycled at high current density of 1 A g -1 , it demonstrates an unprecedented rate capacity with long cycle stability (2190 mAh g -1 after 750 cycles). This paper emphasizes the synergetic effect of in situ electrochemical reconstruction and interfacial lithium storage, which not only offers a new conception for understanding the self-recover capacity phenomenon, but also opens up possibilities for designing high-performance electrodes for LIBs.